Metacognitive writing strategies for vocational high school students - Imas Masyithoh; Eko Suhartoyo (Universitas Islam Malang, 2021)
English writing task for students is considered as the most complex task since they need to combine all English skills on writing construction. Metacognition, the highest order thinking, has to be in writing strategies (planning, monitoring, evaluating). The students who use their metacognition can know which effective writing strategies on doing their writing task. This research aims to elaborate on whether there are significant differences between high and low achievers in writing in using metacognitive writing strategies or not. The researcher selects the Ex-Post Facto research and two instruments; (1) writing test – descriptive text to differentiate between high and low achievers in writing (2) questionnaire – to identify the most and the least uses of metacognitive writing strategies. With the Independent T-test for analyzing the data, the findings are. (1) The uses of metacognitive writing strategies and students’ writing performance are not significantly different. The mean of each strategy had been compared to the mean of students’ performance; moreover, based on the statistical analysis at SPSS, it shows no significant difference. (2)The most used strategy by high and low achievers in writing is planning while the least used strategy is monitoring. From these findings, the null hypothesis is accepted. Although there were no significant differences in the uses of metacognitive writing strategies between high and low achievers in writing, the students have already known effective writing strategies that can improve their writing.